Female homoparenthood: a case study. - Santos, Filomena; Rita Dias; Lurdes Mendes (Abstract from International Conference on Gender and Womens Studies 16 “Interdisciplinary Conference on Gender and Womens Studies in Social Sciences and Art”, November 11-12, Istanbul, 2016)
In Portugal, homoparenthood is an issue that clashes with heteronormativity and therefore does not have social consensus, despite the recent changes in national public policies, as well as in the legal status that allows the adoption of children by same-sex couples. The homoparenthood questions the normative heterosexual and biparental family type; and parental models and more conventional gender roles are rooted in female or male qualities that people believe that only either women or men possess. In order to highlight these questions, we analyse a case study of one homoparental family – a couple of graduated women, both working full-time, and their two little children, who were adopted. We investigate the negotiation of equality in the construction of conjugal and parental roles and identities. Although the roles of both interviewed mothers were different, they were not rigid but flexible and equally shared (house chores, education and childcare). Indeed, is it homosexual parenthood associated with equal conjugal and parental roles within a dynamic democratic family? According to Rodrigues and Paiva (2008), parental roles are not the monopoly of gender roles, instead they are more dependent on the personality of each parent. This is why we highlighted the need of analyse the articulation between individual biographies, interactional and structural factors such as social class and gender. However, since this is an exploratory study, many issues require a broader empirical basis, which means the inclusion of couples of lesbians and gays as well, as well as more social and household diversity.